Academic integrity as a component of preparing higher education students for scientific research in the era of artificial intelligence - Vasiuta, Viktoriia; Vasiuta, Vasyl (Educological discourse, 2026)
The article explores the role of academic integrity as a key factor in preparing higher education students for scientific research in the context of the active implementation of artificial intelligence technologies. The relevance of the topic is due to the digitalization of the educational environment, which transforms traditional approaches to learning, scientific activity and assessment of results, while simultaneously creating new opportunities and risks for compliance with ethical norms. Particular attention is paid to the impact of generative artificial intelligence on the level of independence of education seekers, the formation of their critical thinking and ensuring the reliability of research results.The purpose of the study is to substantiate the role of academic integrity in preparing higher education students for scientific activity and to develop effective mechanisms for its provision, taking into account the opportunities and challenges of using artificial intelligence.. The article summarizes the approaches of Ukrainian and foreign scientists to understanding the essence of academic integrity and analyzes modern trends in its provision in higher education. It was found that the use of artificial intelligence has a dual impact: it contributes to increasing the efficiency of teaching and research, but at the same time creates risks of spreading unethical practices, reducing the level of student independence, and complicating the identification of authorship. Key problems are outlined, including insufficient regulatory certainty, ethical challenges associated with possible algorithmic biases, and the need to adapt educational programs to new conditions. The feasibility of a comprehensive approach to ensuring academic integrity is substantiated, which involves a combination of regulatory, pedagogical, and technological tools. Practical recommendations for higher education institutions are proposed, in particular, the development of clear rules for the use of artificial intelligence, the integration of academic ethics into curricula, the use of modern control tools, and the development of critical thinking among students. The importance of improving the skills of teachers in the ethical use of digital technologies is also emphasized. It is concluded that academic integrity remains the foundation of high-quality higher education, and its effective provision in the context of digitalization is possible only if ethical principles are systematically integrated into all components of the educational process. The results of the study can be used to improve educational policies and practices aimed at forming a responsible and competent scientific community.